If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 2y + -4 Reorder the terms: 15 = -4 + 2y Solving 15 = -4 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 15 + -2y = -4 + 2y + -2y Combine like terms: 2y + -2y = 0 15 + -2y = -4 + 0 15 + -2y = -4 Add '-15' to each side of the equation. 15 + -15 + -2y = -4 + -15 Combine like terms: 15 + -15 = 0 0 + -2y = -4 + -15 -2y = -4 + -15 Combine like terms: -4 + -15 = -19 -2y = -19 Divide each side by '-2'. y = 9.5 Simplifying y = 9.5
| x+8=2x-9 | | -7(3x-6)=210 | | 9x^3-18x^2-69x-3=0 | | -7(-3+7x)=-273 | | =n^2+9n+18 | | 0=1.1y+2.2 | | [x+3.5]=2.5 | | 3+65x-39x=39x+21 | | -2(x-1)=-2x+5 | | 9x^3-45x^2+72x-45=0 | | 1/4(a+7)=8 | | n-9j-7-4n-5j-7= | | 6x+6=-60-5x | | -8(-3n-3)=-8(-4n-8) | | 6(x+24)=2(x+30) | | -24=2x-14 | | =3k^2-33k+72 | | 4k+21=-5 | | 25-3x=10-8x | | 8=z/3+16 | | -2(4-3b)=-8(-b+4) | | 3k^2+73=33k | | -1+3x=-13x | | 2y(4)= | | -8x+2= | | -10q+5y+6-2q-y-6= | | -3(b+7)=6(b+4) | | 0=3x^2-6x+5 | | =(n+2)(2n+5) | | 2-82x=122 | | 2x+ine^4x=12 | | 17x+5=19x-7 |